Effects of protein supplementation on body composition, physiological adaptations, and performance during endurance training: a systematic review and meta-analysis - Xiao, Y.; Deng, Z.; Sun, W.; Li, J.; Gao, W. (Frontiers in Nutrition, 2025)
Introduction: This study aimed to evaluate the long-term effects of endurance training combined with protein supplementation on body composition, physiological adaptations (aerobic/anaerobic capacity), and performance.